Cross - Currency Hedging Using Options - Suri, Akshay (2006)
In today's competitive global markets, most firms are vulnerable to increasing fluctuation in foreign exchange, which is leading them to make use of Currency Derivatives to hedge their risks. Among the several derivatives available, Currency Options are the second most popular instrument used to hedge currency risk. Options are a very distinctive set of instruments that are available to hedge Currency risk. This study provides empirical evidence on why companies employ Currency Options to hedge their risks. It also analyzes the prospective risks and benefits accrued to the parties that undertake currency option as a hedging strategy, how these are valued and why are these preferred over other hedging strategies like forwards and futures and termed as a form of insurance. Additionally, this study also discusses the intricacies involved in Currency Options.